Juvenile justice : advancing research, policy, and practice - Sherman, Francine T., 1955-; Jacobs, Francine Helene (Hoboken, NJ : John Wiley & Sons, 2011)
'Troubled youth intersect with many government systems, but few as frequently and critically as with juvenile justice. This edited volume brings together experts in juvenile justice, child development, and public health to explore the connections between juvenile justice and child health and wellbeing. Unlike other books that focus on deficits, this book advocates tackling the challenges youths face by encouraging the support of family, community, and pre-existing systems to promote growth. Practitioners and policy makers who work with youth will find this positive approach refreshing'--
Includes bibliographical references and indexes.
Keywords: Juvenile justice, Administration of -- United States; Juvenile corrections -- United States; Juvenile delinquents -- United States